Successful endoscopic cyanoacrylate injection therapy for ruptured duodenal varices immediately after balloon‐occluded retrograde transvenous obliteration. Issue 12 (18th November 2021) - Tamai, Yasuyuki; Tanaka, Hideaki; Fujimori, Masashi; Iwasa, Motoh; Nakagawa, Hayato
Abstract: We present a rare case of acute duodenal variceal rupture after B‐RTO that was successfully treated with endoscopic CA injection therapy. A 74‐year‐old Japanese woman was transferred to our hospital due to progressive general malaise and hematemesis. Gastroduodenoscopy (GDS) showed duodenal varices without active bleeding in the second portion of duodenum. Balloon‐occluded retrograde transvenous obliteration (B‐RTO) was carried out to prevent duodenal variceal rebleeding. Good pooling of ethanolamine oleate with iopamidol (EOI) was observed in duodenal varices using balloon catheters. However, massive melena was observed immediately after B‐RTO. Emergent GDS revealed a white plug on the treated varix, thus endoscopic cyanoacrylate (CA) injection therapy was performed. We speculated that the injection of EOI increased the pressure in the duodenal varices which resulted in rupture of duodenal varices. B‐RTO was effective therapy to prevent duodenal variceal rebleeding, but postprocedural monitoring is required as illustrated by this case. We suggest that careful monitoring and backup system for endoscopy are required during or after B‐RTO. Abstract : We present a rare case of acute duodenal variceal rupture after balloon‐occluded retrograde transvenous obliteration (B‐RTO) that was successfully treated with endoscopic cyanoacrylate injection therapy. B‐RTO was effective therapy to prevent duodenal variceal rebleeding, but postprocedural monitoring is required as illustrated by this case. We suggest that careful monitoring and backup system for endoscopy are required during or after B‐RTO.